PENGARUH GAYA HIDUP DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PENGGUNAAN APLIKASI OVO PREMIER PADA MAHASISWA/I DI KOTA MEDAN - Siwi, Indah Raka (JURNAL ADMINISTRASI & MANAJEMEN, 2025)
This research is motivated by the increasing use of OVO application among students in Medan City. This study aims to determine the influence of lifestyle and online customer review on the decision to use OVO application among students in Medan City. This research uses a survey method with a sampling technique using the Lemeshow approach with a maximum estimation of 50% and an error rate of 10%. The sample size in this study consisted of 100 samples. To assess the validity and reliability of the test, 30 consumers were selected from the entire population considered. This research uses a quantitative method. The research method used in this study is a quantitative descriptive research, which aims to analyze thoroughly the subject matter. The results showed that lifestyle and online customer review had a positive and significant effect on the decision to use OVO application among students in Medan City. The coefficient of determination of 0.393 or 39.3% indicates that the combined influence of lifestyle and online customer review in explaining consumer decision is 39.3%. The remaining 60.7% variance may be caused by factors outside the variables studied, such as service quality, discounts, and others. The results of this study can be used as a reference for OVO application developers to improve service quality and increase user trust. Keywords: Lifestyle, Online Customer Review, Usage Decision